The implementation of the "Bologna process" into the subject of animation in tourism, as a significant part of the hotel industry products promotion - Ivkov, Andjelija (Array, 2008)
Summary: Since the academic year 2001/2002, the programme of studies at the Department of Geography, Tourism and Hotel Industry has been adjusted to the requirements of the Bologna Declaration. All the exams, including optional subject Animation in Tourism, during the studies are organised into one-semester exam, and obligatory student's intership has been introduced. Animation in tourism with it's animation programmes, introduces very important segment in touristic offer of one destionation. In this way tourists are able to feel local atmosphere. Also, that is an original instrument to oblige them to have a significant role in creating the "genius loci". In the most hotels and restaurants, on a famous destinations, authentic food is served to guests in the course of animation programmes. The programme should be enriched with the folkloric caracteristics of one nation, which we want to represent to visitors. The main goal of this essay, with theory asppects and concrete examples, is to point out the importance of animation, as a considerable factor and new trend in a process of promoting the hotel product